Arousal frequency is associated with increased fatigue in obstructive sleep apnea - Yue, Herbert J. (Springer-Verlag, 2009)
OBJECTIVE: Fatigue is an important and often underemphasized symptom in patients with obstructive sleep apnea (OSA). Sleep fragmentation, i.e., arousals and disruptions in sleep architecture, is common in patients with OSA and may potentially contribute to their fatigue. We hypothesized that arousal frequency and changes in sleep architecture contribute to the fatigue experienced by patients with OSA. DESIGN: Seventy-three patients with diagnosed but untreated OSA (AHI ≥ 15) were enrolled in this study. A baseline polysomnogram was obtained, and fatigue was measured with the Multidimensional Fatigue Symptom Inventory-short form (MFSI-sf). We evaluated the association between fatigue and arousals and various polysomongraphic variables, including sleep stages and sleep efficiency. RESULTS: Significant correlations between MFSI-sf subscale scores and various arousal indices were noted. Emotional fatigue scores were associated with total arousal index (r = 0.416, p = .021), respiratory movement arousal index (r = 0.346, p = .025), and spontaneous movement arousal index (r = 0.378, p = .025). Physical fatigue scores were associated with total arousal index (r = 0.360, p = .033) and respiratory movement arousal index (r = 0.304, p = .040). Percent of stage 1 sleep and REM sleep were also associated with physical and emotional fatigue scores. Hierarchal linear regression analysis demonstrated that emotional fatigue scores were independently associated with spontaneous movement arousals after controlling for age, body mass index, depression, and sleep apnea severity. CONCLUSIONS: These findings suggest that arousals may contribute to the fatigue seen in patients with OSA.